2006
DOI: 10.1590/s0066-782x2006001600014
|View full text |Cite
|
Sign up to set email alerts
|

Escore de Framingham em motoristas de transportes coletivos urbanos de Teresina, Piauí

Abstract: OBJECTIVETo estimate the absolute risk of the public transportation drivers in the city of Teresina, Piauí, to develop coronary heart disease over the course of ten years based on the Framingham risk score. METHODSAn observational, descriptive, cross-sectional study using the Framingham score was conducted with 107 public transportation drivers in the city of Teresina, Piauí, to assess level of risk and its association with the Framingham predictors that include: age, total cholesterol, HDL cholesterol, systol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 7 publications
1
7
0
8
Order By: Relevance
“…3 The scores found in the calculation of the ERF of young adults revealed two types of results (ERF 1 ERF <% = 1%), and all contained in the classification of low risk for developing CARDIOVASCULAR DISEASE over the next 10 years. Other authors, 7 while investigating the ERF in urban transport drivers in Teresina -Piauí, obtained a majority (85%), and located in the low-risk category. Diverse situation found another study (16) , which found, in the studied population of average age 51.91 years (± 13.25 years), cardiovascular risk by ERF between medium (46.5% and 32%) and high (33.9% and 60%) for minors and people over 60 years old,…”
Section: Resultsmentioning
confidence: 91%
“…3 The scores found in the calculation of the ERF of young adults revealed two types of results (ERF 1 ERF <% = 1%), and all contained in the classification of low risk for developing CARDIOVASCULAR DISEASE over the next 10 years. Other authors, 7 while investigating the ERF in urban transport drivers in Teresina -Piauí, obtained a majority (85%), and located in the low-risk category. Diverse situation found another study (16) , which found, in the studied population of average age 51.91 years (± 13.25 years), cardiovascular risk by ERF between medium (46.5% and 32%) and high (33.9% and 60%) for minors and people over 60 years old,…”
Section: Resultsmentioning
confidence: 91%
“…Essa teoria, aliada ao fator de proteção cardiovascular pela condição hormonal concedida às mulheres adultas, pode explicar a associação do sexo masculino com maior RCV de forma independente encontrada neste estudo e demonstrada por outros autores 11,16,17 . A maior prevalência de RCV elevado esteve presente nas faixas etárias mais avançadas, em especial entre o grupo com 50-59 anos, coincidindo com a literatura em geral 16,[18][19][20] . É bem estabelecido que a incidência de eventos cardiovasculares eleva-se progressivamente conforme a idade 19 , já que o envelhecimento das artérias parece ser proporcional ao envelhecimento do organismo, elevando assim os níveis pressóricos e elevando o RCV 11 .…”
Section: Discussionunclassified
“…O tabagismo é fator de risco considerável para as DCV segundo diversos estudos 11,20,26,27 , já que o mesmo leva a lesão de células endoteliais, prejudicando suas funções, aumentando a rigidez e inflamação arterial, desequilibrando fatores antitrombóticos e trombóticos, beneficiando e antecipando o processo de aterosclerose 26,27 . Entretanto, após o ajuste dos fatores de confusão esta variável perdeu a significância estatística.…”
Section: Discussionunclassified
“…Também foram investigados fatores de risco cardiovasculares (Alquimim, Barral, Gomes, & Rezende, 2012;Benvegnú, Fassa, Facchini, & Breitenbach, 2008;Hirata et al, 2012;Landim & Victor, 2006;G. N. Moraes & Fayh, 2011;Souza & Silva, 2006b, 2006c, nos quais, a idade do trabalhador e o nível de aumento do IMC foram as principais variáveis relacionadas a essas patologias (M. M. Costa et al, 2011).…”
Section: Doenças Cardiovascularesunclassified